2013
DOI: 10.3354/meps10213
|View full text |Cite
|
Sign up to set email alerts
|

Latent effects of hypoxia on the gastropod Crepidula onyx

Abstract: Despite the importance of latent effects in marine invertebrates, no study has considered how larval exposure to hypoxia may have lasting impacts on the individual in later life history stages. In this study, we exposed larvae of the gastropod Crepidula onyx to 2, 3, and 6 mg O 2 l −1 , measured the larval size and total lipid content, transplanted the newly settled individuals to the field, and finally, determined the growth rate, dry weight, and filtration rate of the juveniles after 2 wk in the field. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Stressor events with decreased latency (less lag time) may be more likely to exhibit synergisms or antagonisms. For example, short latencies (2 weeks) in stressors (hypoxia and limited resource availability) applied to gastropod larvae have shown latent effects (Li & Chiu, ). Greater temporal delays between stressors may thus be more likely to result in additive (and therefore predictable) responses, as we found with Olympia oysters.…”
Section: Discussionmentioning
confidence: 99%
“…Stressor events with decreased latency (less lag time) may be more likely to exhibit synergisms or antagonisms. For example, short latencies (2 weeks) in stressors (hypoxia and limited resource availability) applied to gastropod larvae have shown latent effects (Li & Chiu, ). Greater temporal delays between stressors may thus be more likely to result in additive (and therefore predictable) responses, as we found with Olympia oysters.…”
Section: Discussionmentioning
confidence: 99%
“…Along these same lines, the study by Li and Chiu (2013) that was referred to earlier showed that exposing the larvae of Crepidula onyx to hypoxic stress reduced post-metamorphic growth and filtration rates, but only when the stressed larvae had also been reared at a reduced food concentration; larvae exposed to hypoxic stress under high food conditions showed normal post-metamorphic growth, suggesting that having abundant nutrients prior to metamorphosis ameliorated the latent impact of hypoxic stress. Perhaps abundant embryonic nutrient stores also account for the remarkable lack of latent effects seen when brooded embryos of the polychaete Capitella teleta were exposed to severe hypoxia for up to 96 hours .…”
Section: Caution In Interpreting Latent Effectsmentioning
confidence: 75%
“…As hypoxic conditions become increasingly widespread in coastal marine environments around the world, due to climate change and the increasing output of organic wastes and agricultural nutrients (Wu, 2002;Zhang et al, 2013), interest in the potential consequences of spreading hypoxic stress continues to grow. For the calyptraeid gastropod Crepidula onyx, exposing well-fed (2 × 10 5 cells ml -1 ) larvae to oxygen levels as low as 2 mg O 2 l -1 for eight to ten days had no significant impact on the growth rates of field-transplanted juveniles (Li and Chiu, 2013). However, when larvae of this species were exposed to the same level of low-oxygen stress but at reduced food levels (1 × 10 5 cells ml -1 ), subsequent juvenile growth rates and filtration rates were significantly reduced compared with those exhibited by control individuals, even though there were no significant differences in the size or lipid content of juveniles from the different treatment groups at metamorphosis (Li and Chiu, 2013).…”
Section: Latent Effects Following Hypoxiamentioning
confidence: 95%
See 2 more Smart Citations